Bridging the knowledge gap: Attitudes and competencies in palliative care among community health nurses in Urban China - Zhao, Zihan; Diva, Mary Beth P.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
This current study examined the attitudes and knowledge of community health nurses (CHNs) regarding palliative care (PC) and explored key factors influencing these competencies in a non-pilot urban setting in China. A cross-sectional survey was conducted among 206 CHNs in Xuzhou using cluster sampling. Participants completed a demographic questionnaire, the Chinese version of the Frommelt Attitude Toward Care of the Dying Scale (FATCOD-B), and the Palliative Care Knowledge Test (PCKT). Results showed that CHNs held generally positive attitudes (mean FATCOD-B = 103.23 ± 9.25), but demonstrated only moderate knowledge (mean PCKT score = 9.24 ± 2.15; 54.39% accuracy). Regression analysis identified religious beliefs, experience in caring for the terminally ill patients, and PC training as significant predictors of attitude. Knowledge levels were also significantly associated with experience and training. Despite their willingness to provide compassionate care, many nurses lacked formal preparation, especially in opioid use and symptom management. The findings highlight the urgent need for structured education and targeted training programs to enhance PC capabilities among CHNs. Improving these competencies will be critical to expanding access to quality end-of-life care in community settings, particularly in regions not currently prioritized by national policy.